Peningkatan Pelayanan dengan Total Quality Service (TQS) Dalam Meningkatkan Citra PT Arina Multikarya Banjarmasin - Retno Puji Lestari; Anisa Sholatiah; Rahmanisa Juliana; Shanty Komalasari; Musfichin Musfichin (El-Mujtama: Jurnal Pengabdian Masyarakat, 2023)
The community service activities carried out aim to make it easier for guests or prospective applicants to get information by improving company services using the Total Quality system (TQS). This activity was carried out at PT. Arina Multikarya Banjarmasin Branch, which is one of the companies engaged in outsourcing and also marketing that promotes consumer goods, also acts as an agency that houses many employees such as BA (Beauty Advisor), BC (Beauty Consultant), SPG (Sales Promotion Girls) , as well as TL (team leader) from certain companies that have worked together or become company partners. In this community service, the methods used are observation methods, sociological empirical approaches, coordinating and arranging what to do, carrying out activities, and evaluating. From the results of the activity, it shows that the guests who come are greatly helped by the layout of the room and the structure of the employees because the guests who come will find a room for employees. And with posters containing instructions posted in certain places that make guests or prospective employees more orderly. Keywords: Company Image, Quality, Service.